It's a man's world; right? How women's opinions about gender inequality affect physiological responses in men. (April 2022) - Domen, Ilona; Scheepers, Daan; Derks, Belle; van Veelen, Ruth
In two experiments, we examined how men respond to women who either challenge or legitimize societal gender inequality, and how gender identification moderates these responses. We hypothesized that men feel less threatened by women who legitimize (vs. challenge) the gender hierarchy, and evaluate these women more positively. To investigate these expectations, we assessed self-reports (Studies 1 and 2) and cardiovascular threat/challenge responses (Study 2). Both studies showed that men experience less negative emotions when presented with a woman who legitimized (vs. challenged) the gender hierarchy. Moreover, among men with a relatively high gender identification, a woman who challenged the gender hierarchy elicited a physiological response pattern indicative of threat, whereas a woman who legitimized the gender hierarchy elicited a pattern indicative of challenge. Results are discussed in terms of social identity theory, status threat, and self-distancing behavior.